Rowland V. Lee papers - Lee, Rowland V., 1891-1975.
Scripts, reviews, clippings, printed matter, scrapbooks, production stills, photographs, and other papers relating primarily to Lee's career as a silent film actor in Thomas H. Ince productions and as a director, producer, and writer during the period 1917-1959. Includes Lee's scripts for films he directed such as A Thousand to One (1920), The Cup of Life (1921), Desire (1923), Alice Adams (1923), Barbed Wire (1927), Zoo in Budapest (1933), The Count of Monte Cristo (1934), Mother Carey's Chickens (1938), Son of Frankenstein (1939), and Tower of London (1939). Also includes material compiled by Lee to accompany an autobiography on such topics as his career as a silent film actor, his trip to California in 1916, and his military service during World War I; photographs taken during the filming of The Silver Treasure (released 1926); and an annotated copy of Booth Tarkington's book, Alice Adams, used by Lee in preparing his film adaptation of the book; and material pertaining to his last film, The Big Fisherman (released 1959).
Dramatist, actor, and film director and producer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Ince, Thomas H; Drama -- Stories, plots, etc; Motion picture industry; Motion picture plays, American; Motion pictures; Motion pictures -- Production and direction; Silent films; World War, 1914-1918.; California -- Description and travel; Actors; Dramatists; Motion picture directors; Motion picture producers